ASSOCIATION OF LIPID PROFILES AND COGNITIVE FUNCTION DETERIORATION OF GERIATRIC OUTPATIENTS AT NEUROLOGY CLINIC GUNUNGSITOLI REGIONAL GENERAL HOSPITAL - Stefanus Erdana Putra; Berkat Hia; Muhammad Hafizhan; Astrida Fesky Febrianty; Fauzi Novia Isnaening Tyas (The Indonesia Neurological Association Branch of Denpasar, 2021)
Background: The increase of life expectancy in Indonesia causes increasing numbers of dementia, mostly caused by Alzheimer's disease (AD). High serum cholesterol level has been suggested as a risk factor for AD. The strongest evidence linking lipid profile with AD provided by previous experimental studies where adding or reducing cholesterol altered amyloid precursor protein (APP) and amyloid ?-protein (A?) levels is the basic of this research. Objective: To determine whether lipid profile is associated with cognitive function deterioration of geriatric outpatients at Neurology Clinic Gunungsitoli Regional General Hospital. Methods: Participants of this cross-sectional study were outpatient geriatric patients at Neurology Clinic Gunungsitoli Regional General Hospital (n=85; mean age, 62.46±5.49 years old). The cognitive state was evaluated using Montreal Cognitive Assessment Indonesian Version (MoCA-INA) and those with MoCA-INA score <24 were considered cognitively declined. Concentrations of serum lipid profile were measured and correlated with cognitive state using Pearson’s correlation. Multiple logistic regression analysis was used to calculate odds ratios (ORs) for cognitive decline. Results: Based on Pearson’s correlation test, high-density lipoprotein (HDL) level had significant strong positive correlation with MoCA-INA score (r=0.876;p=0.000) and triglyceride level had significant strong negative correlation with MoCA-INA score (r=-0.726;p=0.000). Relatively to cognitive decline, ORs for decreased HDL level was 3.19 (95%CI 2.02-4.36) and increased triglyceride level was 2.59 (95%CI 1.29-3.91). Conclusion: There was a significant relationship between decreased HDL-cholesterol level and increased triglyceride level with cognitive decline in geriatric outpatients.